New Words in Interaction of Languages and Cultures - L I Bogdanova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2015)
The article deals with the problem of functionality of new words and their ability to fill the language gap and meet functional needs. The study examines the revitalization process of lexical and phraseological units (mostly borrowed) under the influence of new media. It was revealed that new words are used to indicate important aspects of modern life, among which a special place is occupied by an interest in the future, the need for long-term planning, the need for understanding the concept of success / failure, and others. The analysis enables the authors to make observations about the nature of an unstable relationship between the cognitive and the evaluative compounds of the meanings of the selected terms. The methodology of our study is based on onomasiological approach to language learning by relying on the definitional analysis, component analysis and modeling method. The material was taken from the language of mass media, dictionaries of the Russian language and Internet sources. This study is promising, because it gives an opportunity to reveal the cognitive mechanisms of forming new meanings demanded by society and getting accepted as new lexical and phraseological units